Autonomous State : The Struggle for a Canadian Car Industry from OPEC to Free Trade - Anastakis, Dimitry, 1970- (Book collections on Project MUSE., 2013)
More than just an examination of the auto industry, the book provides a rethinking of Canada's tumultuous post-OPEC political and economic evolution, helping to explain the current tribulations of the global auto sector and Canada's place within it.